Comparison of the effects of submucosal hyaluronidase and dexamethasone on postoperative edema, pain, trismus, and infection following impacted third molar surgery - Onur Koç; Nuray Er; Çiğdem Karaca; Kanİ Bilginaylar (BMC, 2024)
Abstract Background Limiting postoperative edema, pain, trismus, and infection is crucial for smooth healing. This prospective, controlled clinical trial investigated and compared the effectiveness of dexamethasone and hyaluronidase in relieving these complications. Methods In groups Ia and IIa, 8 mg of dexamethasone and 150 IU of hyaluronidase were administered following the removal of impacted teeth, respectively. The contralateral sides (groups Ib and IIb) were determined as control groups. Edema, pain, trismus, and infection were clinically evaluated on the 1st, 2nd, 3rd, and 7th postoperative days. Results 60 patients were enrolled in the study. Hyaluronidase provided significantly more edema relief than dexamethasone on the 1st, 2nd, 3rd, and 7th postoperative days (P = 0.031, 0.002, 0.000, and 0.009, respectively). No statistical difference was found between dexamethasone and hyaluronidase in VAS and rescue analgesic intake amount values for all time points. Hyaluronidase was more effective in reducing trismus than dexamethasone on the 2nd and 3rd postoperative days (P = 0.029, 0.024, respectively). Neither of the agents significantly increased the postoperative infection rate. Conclusions Hyaluronidase can be selected when postoperative excessive edema and trismus are anticipated. Dexamethasone may be a cost-effective option if postoperative pain control is merely targeted. Trial registration This trial was registered in the Clinical Trials Protocol Registration and Results System (ClinicalTrials.gov identifier number: NCT05466604) on 20/07/2022.